Cost‐effectiveness of noninvasive fetal RhD blood group genotyping in nonalloimmunized and alloimmunized pregnancies. Issue 5 (16th February 2022) - Gajic‐Veljanoski, Olga; Li, Chunmei; Schaink, Alexis K.; Guo, Jennifer; Shehata, Nadine; Charames, George S.; de Vrijer, Barbra; Clarke, Gwen; Pechlivanoglou, Petros; Okun, Nanette; Kandel, Rita; Dooley, Joseph; et al.
Abstract: Background: We sought to determine the cost‐effectiveness of noninvasive fetal RhD blood group genotyping in nonalloimmunized and alloimmunized pregnancies in Canada. Study design and methods: We developed two probabilistic state‐transition (Markov) microsimulation models to compare fetal genotyping followed by targeted management versus usual care (i.e., universal Rh immunoglobulin [RhIG] prophylaxis in nonalloimmunized RhD‐negative pregnancies, or universal intensive monitoring in alloimmunized pregnancies). The reference case considered a healthcare payer perspective and a 10‐year time horizon. Sensitivity analysis examined assumptions related to test cost, paternal screening, subsequent pregnancies, other alloantibodies (e.g., K, Rh c/C/E), societal perspective, and lifetime horizon. Results: Fetal genotyping in nonalloimmunized pregnancies (at per‐sample test cost of C$247/US$311) was associated with a slightly higher probability of maternal alloimmunization (22 vs. 21 per 10, 000) and a reduced number of RhIG injections (1.427 vs. 1.795) than usual care. It was more expensive (C$154/US$194, 95% Credible Interval [CrI]: C$139/US$175‐C$169/US$213) and had little impact on QALYs (0.0007, 95%CrI: −0.01–0.01). These results were sensitive to the test cost (threshold achieved at C$88/US$111), and inclusion of paternal screening. Fetal genotyping in alloimmunized pregnancies (at test cost of C$328/US$413) was less expensive (‐C$6280/US$7903, 95% CrI: ‐C$6325/US$7959 to ‐C$6229/US$7838) and more effective (0.19 QALYs, 95% CrI 0.17–0.20) than usual care. These cost savings remained robust in sensitivity analyses. Discussion: Noninvasive fetal RhD genotyping saves resources and represents good value for the management of alloimmunized pregnancies. If the cost of genotyping is substantially decreased, the targeted intervention can become a viable option for nonalloimmunized pregnancies.